Peripheral Vascular Disease: The Role of MR- Angiography - Economopoulos, Nikolaos; Brountzos, Elias N.; Kelekis, Nikolaos L. (Current Medical Imaging, 2006)
Magnetic Resonance Angiography (MRA) with intravenous paramagnetic agent has recently evolved as an accurate non invasive method, for the imaging of the aorta and its major branches, the carotid, the renal and pelvic arteries. The first report of contrast enhanced MRA was published at 1993. Recently a new method was developed, employing the motion of the MR table, during the examination (Moving bed - bolus chase MRA) which permits the imaging of the total length of the abdominal aorta down to the plantar arches. In patients with critical ischemia, it is critical to visualize the arteries beyond the trifurcation as well as the plantar arch, in order to decide whether to perform distal bypass or to amputate. However, transcatheter angiography commonly cannot depict the patency of a small caliber vessel, beyond the occlusion (runoff vessel). This vessel is called angiographically occult vessel and its depiction is critical for the surgical anastomosis. MRA is capable to detect very small amounts of paramagnetic agent within the vessel lumen, thus enabling the depiction of small caliber vessels. Nevertheless some problems need special attention, foremost of which is the early venous filling (venous contamination), occuring commonly in the diabetic patient population. The main advantages of MRA include the absence of ionizing radiation, and the avoidance of nephrotoxic contrast media.
Keywords: peripheral vessels